Is Protectionism on the Rise? Assessing National Trade Policies during the Crisis of 2008 - Kee, Hiau Looi; Neagu, Cristina; Nicita, Alessandro (MIT Press, 2014)
This paper quantifies trade policy changes and the associated trade impacts for about 100 countries between 2008 and 2009. Results show that there has been no widespread increase in protectionism. Only a few countries, including Russia, Argentina, Turkey, and China, have increased tariffs on major imported products. The United States and the EU, by contrast, rely mainly on antidumping duties to shield domestic industries. Overall, while the rise in tariffs and antidumping duties may have jointly caused global trade to drop by US$43 billion, it explains less than 2% of the collapse in world trade during the crisis period.